Reversible Electrochemical Modulation of a Catalytic Nanosystem. (29th July 2016) - della Sala, Flavio; Chen, Jack L.‐Y.; Ranallo, Simona; Badocco, Denis; Pastore, Paolo; Ricci, Francesco; Prins, Leonard J.
Abstract: A catalytic system based on monolayer‐functionalized gold nanoparticles (Au NPs) that can be electrochemically modulated and reversibly activated is reported. The catalytic activity relies on the presence of metal ions (Cd 2+ and Cu 2+ ), which can be complexed by the nanoparticle‐bound monolayer. This activates the system towards the catalytic cleavage of 2‐hydroxypropyl‐ p ‐nitrophenyl phosphate (HPNPP), which can be monitored by UV/Vis spectroscopy. It is shown that Cu 2+ metal ions can be delivered to the system by applying an oxidative potential to an electrode on which Cu 0 was deposited. By exploiting the different affinity of Cd 2+ and Cu 2+ ions for the monolayer, it was also possible to upregulate the catalytic activity after releasing Cu 2+ from an electrode into a solution containing Cd 2+ . Finally, it is shown that the activity of this supramolecular nanosystem can be reversibly switched on or off by oxidizing/reducing Cu/Cu 2+ ions under controlled conditions.